Evaluation of Prevalence and Risk Factors for Postpartum Depression Using the Edinburgh Postpartum Depression Scale: A Cross-Sectional Analytic Study - Kahveci, Gaye; Kahveci, Bekir; Aslanhan, Hamza; Bucaktepe, Pakize Gamze Erten (Gynecology Obstetrics & Reproductive Medicine, 2021)
Objective: To evaluate the prevalence and associated risk factors for postpartum depression (PPD) using the Edinburgh Postpartum Depression Scale (EPDS). Study design: The population of this cross-sectional analytic study consisted of 311 women who were admitted to our hospital at 4-6 weeks after birth. The data were collected between April-June 2018 by applying a sociodemographic data form consisting of 44 questions and the EPDS consisting of 10 questions. We used the EPDS in postpartum period to divide parturients into those with (n=47) and without (n=264) PPD using a cut-off score of ³ 13. The primary outcome is the prevalence of PPD, while the secondary outcomes are associated risk factors. Results: The PPD prevalence was 15.1% (n=47). In the PPD group, the difference was highly significant in terms of abortion, antenatal depression, inadequate care for the baby and health problem in the newborn [0.6±0.9 vs. 0.2±0.6, 13 (37.1%) vs. 27 (10.5%), 9 (56.3%) vs. 38 (12.9%), 12 (36.4%) vs. 35 (12.6%), respectively] (p<0.001). The logistic regression analysis revealed that abortion increased PPD by 1.64 fold (1.13-2.37% at 95% CI), antenatal depression by 5.04 fold (2.38-10.68% at 95% CI), inadequate care for the baby by 6.28 fold (1.89-20.86% at 95% CI), and health problem in the newborn increased PPD by 3.59 fold (1.43-8.99% at 95% CI). Conclusion: PPD is a health problem that can affect primarily mother and child. Therefore, it is important to determine highly predictable risk factors using a scale (e.g. EPDS) for early diagnosis and timely treatment of symptoms.